2010
DOI: 10.3748/wjg.v16.i16.2065
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatitis in pregnancy: An unresolved issue

Abstract: Management of acute pancreatitis in pregnancy is based on expert opinion only, due to geographic and ethic variations. Nonbiliary causes should be sought as they are associated with worse outcomes. Alcohol as a cause of acute pancreatitis is not rare. Hemoconcentration as a marker of fluid deficit and severity should be predicted with caution and fluid resuscitation should be done carefully by closely monitoring the central venous pres sure, cardiac and respiratory system. Hypercalcemia of hyperparathyroidism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…An observational study of 54 pregnant patients with AP showed that HL is associated with more intrauterine fetal distress and worse fetal outcomes compared with AP from other etiologies (13). Severe pancreatitis is often complicated by varying degrees of multi-organ failure such as acute respiratory failure, acute renal failure, heart failure and arrhythmias, gastrointestinal bleeding, and pancreatic encephalopathy (3). SAP is a serious complication during pregnancy and the main cause of maternal and fetal death, with its fetal mortality rate at 10-30% (14).…”
Section: Treatment and Diagnosis Of Hyperlipidemia Acute Pancreatitis...mentioning
confidence: 99%
See 1 more Smart Citation
“…An observational study of 54 pregnant patients with AP showed that HL is associated with more intrauterine fetal distress and worse fetal outcomes compared with AP from other etiologies (13). Severe pancreatitis is often complicated by varying degrees of multi-organ failure such as acute respiratory failure, acute renal failure, heart failure and arrhythmias, gastrointestinal bleeding, and pancreatic encephalopathy (3). SAP is a serious complication during pregnancy and the main cause of maternal and fetal death, with its fetal mortality rate at 10-30% (14).…”
Section: Treatment and Diagnosis Of Hyperlipidemia Acute Pancreatitis...mentioning
confidence: 99%
“…Acute pancreatitis (AP) is an inflammatory process affecting the pancreas and is characterized by severe abdominal pain and increased levels of amylase and lipase (1). AP in pregnancy (APIP) is a rare complication (incidence between 1 in 12,000 and 1 in 1,000) that threatens the health of the patient and their offspring (2,3). APIP is associated with increased risk of prematurity, preeclampsia, post-partum hemorrhage, maternal death and fetal demise.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with alcoholic pancreatitis, the activity of gamma glutamyl transpeptidase may be increased. Increase in ALT levels by three times the normal, strongly suggests the diagnosis of biliary pancreatitis [28,29]. The triglyceride levels >1000 mg/dl (11.3 mmol) are associated with pancreatitis.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Antibiotics are not used prophylactically in every patient [36,37]. However, when indicated as in documented necrotizing pancreatitis, meta-analysis has indicated that imipenum/ cilastin are the most appropriate antibiotics [37,39]. Even though there are no studies indicating the proposed dose, a dose adjustment for pregnancy is advised [39].…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation